THE VARIOUS FACTORS AFFECTING BHESHAJA MATRA (DOSE) AND THE IMPORTANCE OF DASAVIDHA PARIKSHA IN DECIDING THE PROPER MATRA - *Rama Krishna Allam; Hema Sundari.Ch; Vishwanath J; Dixit Renu; Reddy K.V.V.Bhaskara (International Journal of Ayurveda and Pharma Research, 2015)
The success of treatment depends on dosage, time and proper administration (Yukti). Every wise physician gives importance to these two factors Matra and Kala, where Matra is prime one. Aushadha is one among the four Chatuspada. If it is properly used in Samyak matra, it cures diseases. If it is used in Atimatra, it may harm body or excreted by Malamarga. Same way if it is used in Hina matra, may not be capable to cure the disease. It is the Matra only by which Visha becomes Amrta and vice versa Ausadha becomes Visha.The Matra depends on various factors like Dosha, Agni, Bala, Vaya, Vyadhi, Dravya, Bala, Satva, Desha and Kostha etc. To take maximum benefit of Ausadha one should have to consider these all above while examining the Atura. These can be correlated with modern Pharmacology factors like age, weight, surface area, and enzymatic action etc. These factors can be compiled in the Balacatustaya namely Dehabala, Agnibala, Chittabala and Rogabala.Dasavidha Atura Pariksha is most scientific, complete and competent approach to clinical examination, because it is integration of both Roga Pariksa and Rogi Pariksa. It elicits an accurate account of Vyadhibalapramana and set this against the background of Aturabalapramana, which helps in deciding proper Matra.